Influential Article Review - Exploring Concrete and Abstract CSR Initiatives - Fleming, Pat; Leonard, Derek; Sherman, Tommie (Journal of Leadership, Accountability and Ethics, 2019)
This paper examines corporate social responsibility and diversity. We present insights from a highly influential paper. Here are the highlights from this paper: Guided by Hofstede’s (Culture’s consequences: Comparing values, behaviors, institutions, and organizations across nations, 2001) cultural value of uncertainty avoidance, this study tests whether the effect of concrete vs. abstract CSR campaign messages on attitude toward the company and purchase intention varies by cultural difference in uncertainty avoidance and whether such effect is mediated by the perceived clarity of the message and perceived CSR. Lab experiments were performed in the U.S. and South Korea with American and Korean college students. Two-way ANOVA results revealed the relative advantage of concrete message on attitude toward the company and purchase intention among Koreans (vs. Americans) with high (vs. low) uncertainty avoidance. A series of bootstrap analysis testing multiple mediation models showed that the relative advantage of concrete message among Koreans was mediated by their perceived message clarity and perceived CSR in response to the concrete message. By identifying an international CSR campaign message strategy, the findings contribute to research on cross-cultural campaigns and CSR campaign effects. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.